Optimizing sensory fiber activation during cervical transcutaneous spinal stimulation using different electrode configurations: A computational analysis. Issue 10 (7th June 2022) - de Freitas, Roberto M.; Capogrosso, Marco; Nomura, Taishin; Milosevic, Matija
Abstract: Background: Cervical transcutaneous spinal cord stimulation (tSCS) is a rehabilitation tool which has been used to promote upper‐limb motor recovery after spinal cord injury. Importantly, optimizing sensory fiber activation at specific spinal segments could enable activity‐dependent neuromodulation during rehabilitation. Methods: An anatomically realistic cervical tSCS computational model was used to analyze the activation of α‐motor and Aα‐sensory fibers at C7 and C8 spinal segments using nine cathode electrode configurations. Specifically, the cathode was simulated at three vertebral level positions: C6, C7, and T1; and in three sizes: 5.0 × 5.0, 3.5 × 3.5, and 2.5 × 2.5 cm 2, while the anode was on the anterior neck. Finite element method was used to estimate the electric potential distribution along α‐motor and Aα‐sensory fibers, and computational models were applied to simulate the fiber membrane dynamics during tSCS. The minimum stimulation intensity necessary to activate the fibers (activation threshold) was estimated and compared across cathode configurations in an effort to optimize sensory fiber activation. Results: Our results showed that nerve fibers at both C7 and C8 spinal segments were recruited at lower stimulation intensities when the cathode was positioned over the C7 or T1 vertebra compared with the C6 position. Sensory fibers were activated at lower stimulation intensities using smaller electrodes, which could also affect the degree of nerve fiber activation across different positions. Importantly, Aα‐sensory fibers were consistently recruited before α‐motor fibers. Conclusions: These results imply that cathode positioning could help optimize preferential activation of hand muscles during cervical tSCS. Abstract : In this study, we concluded that: The C7 or T1 cathode positions optimized the activation of sensory fibers projecting to the hand muscles. Smaller cathodes required less intensity to activate the fibers, which could affect the degree of activation across different positions. Sensory fibers were always recruited at lower stimulation intensities compared with motor fibers for all cathode configurations.